[Rezension von: Chris L. de Wet, Preaching bondage: John Chrysostom and the discourse of slavery in early Christianity] - Ritter, Adolf Martin (de Gruyter, 2016)
Chris L. de Wet: Preaching bondage: John Chrysostom and the discourse of slavery in early Christianity, Oakland (University of California Press) 2015, XIII + 329 S., ISBN 978-0-520-28621-4, $ 95
In: Zeitschrift für Antikes Christentum / Journal of ancient christianity, 20 (2016), Nr. 3. pp. 564-571. ISSN 0949-9571 (Druck-Ausg.); 1612-961X (Online-Ausg.)
Keywords: Rezension